USE OF VIRTUAL ENVIRONMENT AND 3D MULTIMEDIA ELECTRONIC TEXTBOOKS IN HIGHER EDUCATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The purpose of this article is to provide an overview of the educational possibilities of the virtual world and metaverses in education, paying special attention to their pedagogical possibilities.